Consórcios públicos municipais como estratégia de desenvolvimento local: possibilidade de consorciamento na visão dos gestores municipais - Teles, Tiana Figueiredo (2019)
The redemocratization process, inaugurated in Brazil with the promulgation of the 1988 Citizen Constitution, promoted important changes in the political, fiscal and administrative context of Brazil. The reconfiguration of intergovernmental relations established independence between the federated entities and regulated the redistribution of constitutional competences with a view to promoting the democratization of local governments. The greater autonomy and responsibilities of the federated entities made possible by the lack of development policies, especially of the municipalities, ended up widening the financial, political and administrative disparities that mainly compromise the guarantee of access to public services. In this context, the process of inter-municipal cooperation, in the form of Public Consortium, emerged as an alternative to the optimized management of public services. The process of cooperation between the federated entities, which was initially marked by informality and flexibility, emerged as an institute with Law 11.107 / 2005, known as the Public Consortium Law. The law reinforces the expansion of the Consortium's potential for action and guarantees access to the public service, as well as presents potential for promoting regional development. Thus, the present study aimed to verify how the implementation of an inter-municipal consortium in the sergipe central agreste could promote improvements and opportunities for local and regional development, especially with the municipalities involved. The results showed that, in the cities surveyed, managers only know the Public Consortium in a superficial way and are unaware of the steps necessary for their constitution. The data also allowed us to verify that, although all the municipalities surveyed are part of a certain type of Consortium, participation did not occur voluntarily and there is also a shortage of State and Federal resources and incentives for consortiums. Based on the information obtained, the study concluded that Public Consortia are a viable alternative to the implementation of public policies since municipalities share similar difficulties, but this can only become feasible if there is a process of awareness and training of the municipal public manager benefits and legal procedures of the whole process.